Dynamics of crypto mining - Harju, Lassi (My University, 2024)
This thesis studies the role of crypto mining in enabling the crypto phenomenon. Cryptocurrencies and blockchain technology were first described in 2008 by Satoshi Nakamoto in the Bitcoin whitepaper. The Bitcoin network was deployed at the beginning of 2009. It uses the Proof of Work consensus mechanism to validate data and secure the network in an anonymous and decentralized manner. Crypto mining is the process of repeated hash calculation that secures the network and validates data. Depending on the cryptocurrency and network maturity, various types of equipment are used to calculate the hashes. Currently, Bitcoin mining is done with ASIC-miners that are purpose-built for repeated hash calculations. The issues of the Proof of Work consensus mechanism are often discussed and presented as major limitations of the technology. Although Proof of Work is recognized as a central piece of blockchain technology, its role in enabling the crypto phenomenon is poorly understood and researched. This thesis looks at bitcoin mining from the environmental, financial, and community perspectives to establish whether mining has played an enabling role in the rapid rise of cryptocurrencies. The environmental perspective consists of a literature review on the environmental impact of Bitcoin. The financial perspective calculates the gross profit of Bitcoin mining at various points in time. The community perspective analyses crypto and mining related communities and search trends to establish whether mining aids in community creation. Bitcoin provides the most applicable and widely adopted data point on Proof of Work cryptocurrencies. The thesis finds that although the issues of Proof of Work are often presented as major limitations of the technology, at least currently they do not appear to have a major negative impact on the technology. The thesis concludes that mining has in part enabled the rise and popularity of the blockchain and cryptocurrencies, but further research on the matter is required to establish the extent of the contribution.

Tämä diplomityö tarkastelee kryptolouhinnan roolia ja vaikutusta kryptovaluutat mahdollistavana tekijänä. Kryptovaluutat ja lohkoketjuteknologia kuvailtiin ensimmäisen kerran vuonna 2008 Satoshi Nakamoto -nimimerkillä julkaistussa artikkelissa nimeltä ”Bitcoin Whitepaper”. Bitcoin-verkko julkaistiin vuoden 2009 alussa. Se käyttää konsensusprotokollana työtodistusta, jolla taataan verkon turvallisuus ja tietojen oikeellisuus. Tiivistefunktioiden toistuvaa laskemista kutsutaan louhinnaksi. Kryptovaluutasta ja verkon kehityksestä riippuen, kryptovaluuttoja voi louhia tavanomaisilla tietokoneillakin. Nykyään bitcoineja voi käytännössä louhia vain tarkoitukseen erityisesti kehitetyillä laitteilla. Työtodistusprotokollan puutteista ja ominaisuuksista keskustellaan usein, ja ne esitetään merkittävinä haasteina teknologian tulevaisuudelle ja kehitykselle. Vaikka työtodistus tunnistetaan keskeiseksi osaksi kryptovaluuttoja, sen laajempi rooli kryptovaluutat mahdollistavana tekijänä on heikosti ymmärretty. Tämä diplomityö analysoi louhinnan roolia ilmasto-, talous- sekä yhteisönäkökulmista. Tarkoituksena on selvittää, onko kryptolouhinta osaltaan toiminut teknologian kehitystä ja käyttöönottoa tukevana vai rajoittavana tekijänä. Ilmastonäkökulma tarkastelee Bitcoin verkon sähkönkulutuksesta tehtyjä tutkimuksia kirjallisuuskatsauksella. Talousnäkökulmassa analysoidaan Bitcoin-louhijoiden tuottavuutta eri ajankohtina. Yhteisönäkökulma analysoi kryptovaluuttojen ympärille rakentuneita ryhmiä ja hakukonetilastoja tarkoituksena selvittää, minkälainen rooli louhinnalla on yhteisöjen synnyssä ja valuuttojen suosiossa. Bitcoinia käytettiin tutkimuksen kohteena, koska se on tunnetuin, yleisimmin ja pisimpään käytössä oleva työtodistuskryptovaluutta. Tutkimuksen tulokset osoittavat, että vaikka työtodistusprotokollan ominaisuuksia pidetään usein erittäinkin ongelmallisina, eivät ne näytä vaikuttava negatiivisesti verkon kehitykseen. Lopuksi työssä todetaan, että louhinta on osaltaan mahdollistanut kryptovaluuttailmiön ja lohkoketjujen suosion, mutta lisätutkimusta vaaditaan, jotta merkittävyyttä voitaisiin arvioida paremmin.
Keywords: bitcoin, crypto, cryptocurrency, crypto mining, proof of work, environmental impact, financial, community, bitcoin, krypto, kryptovaluutta, louhinta, työtodistus, ilmastovaikutukset, talous, yhteisö